Recovering the Body : A Philosophical Story - CAROL COLLIER (University of Ottawa Press, 2013)
it been more urgent to be enlightened by a philosophical nreflection on the body. Confronted with such crucial issues as organ traffic, organ donation, assisted suicide and biomedical research, citizens, politicians and policy makers certainly need solid scientific evidence to justify their decisions. But, first and foremost, actors in the public forum need to identify what the real issues are. this cannot be accomplished without getting at a problem’s philosophical underpinnings. too often, solutions address only pseudo-problems. take this line of reasoning, for example: there is a shortage of organs; therefore we should implement policies and programs for the purpose of increasing the availability of organs. While this assertion makes sense in and of itself, most politicians, policy makers and citizens fail to see that this kind of assertion results from a philosophical discourse on the body, which itself rarely becomes the subject of an enlightened public discussion. Why? Because philosophy itself is part of the problem.